Application of Group Activity Therapy in Improving Social Interaction Skills in Patients With Social Isolation at UPT Bina Laras Pasuruan - Wuryandari, Astrid Ayu; Ibad, M. Rosyidul (Jurnal Kesehatan dan Kedokteran, 2025)
Social isolation is a major nursing problem in patients with schizophrenia, characterized by withdrawal, limited interaction, and impaired social functioning. This condition may interfere with the rehabilitation process and reduce patients’ ability to adapt socially. Objective: This study aims to evaluate the effectiveness of Group Activity Therapy in improving social interaction skills among patients with social isolation at UPT Bina Laras Pasuruan. Methodology: This study used a case study design involving five patients diagnosed with social isolation. Data were collected through direct observation of behavioral symptoms and communication abilities before, during, and after the intervention. The therapy was conducted over two weeks in 30-minute sessions using the Nursing Action Implementation Strategy and six structured group activity sessions. Findings: The results showed a marked reduction in symptoms of social isolation. Of the nine symptoms identified on the first day, only two remained by the eleventh day, namely limited eye contact and purposeless movements. Patients also showed progressive improvement in verbal and non-verbal communication, including introducing themselves, initiating conversations, maintaining appropriate posture, and participating actively in group activities. Implications: Group Activity Therapy can be applied as an effective non-pharmacological nursing intervention in psychiatric rehabilitation settings to improve social interaction, communication, and interpersonal functioning. Originality: This study provides practical evidence that a structured and staged group therapy approach can produce measurable behavioral improvements in patients with schizophrenia experiencing social isolation.